Controls of Accounting Information Systems and Their Role in Reducing Financial Data Manipulation and Improving the Quality of Accounting Reports: An Applied Study at Al-Mansour Investment Bank for the Period (2017–2024) - Hala AbdulAmeer Dhahir (Journal of Advances in Accounting, Economics, and Management, 2025)
This research Aims to study controls security systems Information accounting and its role in limit from manipulation with data finance and improve quality reports accounting, with the focus on an experience bank Al-Mansour For investment during period 2017-2024. Done. Accreditation on Curriculum Applied And analytical, where included Search collection Data from during Surveys and interviews with employees And officials Systems Information And review Finance, In addition to study Reports Finance For the period Studied . Showed. results Search that application Controls security systems Iinformation accounting shares In a way big in reduction Opportunities manipulation With data Finance, And raise accuracy and reliability Reports Accounting . As well. Bent Results that Controls like Control in Access, Review Interior, documentation Operations Finance, And alerts order Automatic she has effect positive on transparency Information accounting And its quality . Search to that Strengthening Controls security Systems Information accounting It is considered from Factors Basic To maintain on safety Data Finance, to support take decision Financial, And more trust between investors And customers . foot Search group from Recommendations The process To enhance effectiveness Controls in Banks, including Guarantee protection Data Finance And improve quality Reports accounting.